Political economy of agriculture and food policy in Africa - Resnick, Danielle (Annual Reviews, 2024)
This article reviews the literature on the political economy of agricultural and food policy in sub-Saharan Africa. In doing so, it first presents a conceptual framework highlighting that agricultural and food policy decisions are contingent on the intersection between governance structures, the preferences and pressures from societal interest groups, and international dynamics. The interrelations among these three factors are then examined across several different sets of policy instruments that have been the focus of traditional political economy research in the region: trade, tax, and marketing policies; public investments and regulations; input and food subsidies; and cross-cutting policies for value chain development. Recognizing several broader demographic, technology, and governance transitions in the region, the article also highlights key areas for future analysis that examine the role of cities in food policy, the possibilities presented by expanded mobile phone and Internet access, and the efficacy of new public administration modalities for policy implementation.